Online generation and control of quasi-static multi-contact motion by PWT Jacobian matrix with contact wrench estimation and joint load reduction*. (2nd January 2021) - Hiraoka, Naoki; Murooka, Masaki; Noda, Shintaro; Okada, Kei; Inaba, Masayuki
Abstract : In this paper, we propose a generic method of online motion generation and control that realizes quasi-static multi-contact motion for real position-controlled humanoids. The proposed system calculates command joint angle online by prioritized inverse kinematics that realizes the target contact states and the target position/orientation of interaction end-effectors feasibly. In order to enable control of contact wrench and joint torque with position-controlled robots, Jacobian matrixes (PWT Jacobian matrix) focusing on relationships between command joint angle and actual joint position, contact wrench, and joint torque are introduced. In addition, contact wrench is estimated at the body parts where force sensors are not mounted to enable contacts there, and joint load reduction based on the motor temperature is taken into account to enable long-term motions with real humanoids. The proposed method was verified by a real life-size position-controlled humanoid HRP2-JSKNTS, and various multi-contact motions such as desk climbing using the right knee and both arms were realized. GRAPHICAL ABSTRACT: UF0001